2016
DOI: 10.1039/c5pp00412h
|View full text |Cite
|
Sign up to set email alerts
|

A study on bioluminescence and photoluminescence in the earthworm Eisenia lucens

Abstract: Eisenia lucens is an earthworm living in the organic soil layer of decomposing wood. When irritated, the worm expels coelomic fluid through pores in its body wall, exhibiting blue-green bioluminescence. The mechanism of the bioluminescence, which seems to be different from other bioluminescence systems of terrestrial animals, has been studied in this work. Many lines of evidence indicate that riboflavin stored in coelomycetes plays an important role in this glowing reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…In a most recent paper, Pes et al report blue-green luminescence of Eisenia lucens upon stimulation with ethanol. These authors also state that riboflavin stored in coelomocytes plays an important role in the glowing reaction (38).…”
Section: First Laboratory Studies Of Earthworm Luminescencementioning
confidence: 98%
“…In a most recent paper, Pes et al report blue-green luminescence of Eisenia lucens upon stimulation with ethanol. These authors also state that riboflavin stored in coelomocytes plays an important role in the glowing reaction (38).…”
Section: First Laboratory Studies Of Earthworm Luminescencementioning
confidence: 98%
“…A total absence from soil samples collected at 2 sites (I and III) and from the others during the spring and early summer may indicate no more than this earthworm was not in the mineral soil. Previous records (Pes et al 2016;Szederjesi et al 2018) and our own collection for laboratory experiments in 2013 and 2017, showed that a large component of the life cycle of this earthworm is enacted within rotting wood above the soil surface. To assess this fully, more than just hand-sorting of soil from a given area plus addition of a vermifuge is required.…”
Section: Fieldworkmentioning
confidence: 85%
“…Riboflavin exists in the cytoplasm of coelomocytes with different contents among earthworm species of various genera [33]. The secreted mucus from intersegmental pores and mouths also produces fluorescence [29,34,35]. Since riboflavin is essential to the regeneration, the stem cells responsible for regeneration accumulate more riboflavin than other cells thus inducing stronger autofluorescence [36].…”
Section: Annelidamentioning
confidence: 99%